EFFECT OF FOLIC ACID INTAKE DURING PREGNANCY WHOSE MOTHER WAS EXPOSED TO CIGARETTE SMOKE TOWARDS BRAIN NEURONS APOPTOSIS INDEX AND QUANTITY OF MICE OFFSPRING (Mus musculus) - Nyna Puspita Ningrum (Communication and Social Dinamics (CSD), 2017)
Folic acid contain 5-methyltetrahydrofolate (5-MTHF) which is one of the antioxidants that can be used to inhibit the reaction that caused by cigarette smoke exposure, inhibit the levels of Reactive Oxygen Species (ROS) so as to reduce the occurrence of neuronal apoptosis. The objectives of this study was to determine the effect of folic acid intake during pregnancy whose mother is exposed to cigarette smoke toward brain neurons apoptosis index and quantity of mice offspring (Mus musculus). Study methods was using experimental laboratory study with posttest-only control group design, the subjects were 24 female mice divided into 4 groups consisting of one control group and three treatment groups. Sampling using simple random sampling, each group consisting of 6 animal. control group 1 were not given treatment during pregnancy, group 2 were given folic acid orally on days 0-17 of gestation age as much as 0,06 mg/day/mice, group 3 were given cigarette smoke exposure on days 7-17 of gestation age amounting to 2 cigarettes/day, groups 4 were given cigarette smoke exposure on days 7-17 of gestation age amounting to 2 cigarettes/day and folic acid orally on days 0-17 of gestation age as much as 0,06 mg/day/mice. The result showed significant differences in all variables. In the neurons apoptosis index there are significant differences between groups 1 and 3, groups 2 and 3, groups 3 and 4, significant differences in the quantity of neurons between groups 1 and 3, groups 2 and 3, groups 2 and 4. The study concluded that there were significant difference in neural apoptosis index between all groups, and there were also significant differences in the quantity of neurons between all groups. Keywords: Cigarette smoke exposure, Folic acid, Apoptosis index, Quantity of neurons